2012
DOI: 10.1128/jb.00087-12
|View full text |Cite
|
Sign up to set email alerts
|

Genome Sequence of Paenibacillus sp. Strain Aloe-11, an Endophytic Bacterium with Broad Antimicrobial Activity and Intestinal Colonization Ability

Abstract: Paenibacillus sp. strain Aloe-11, a Gram-positive, spore-forming, facultatively anaerobic bacterium isolated from the root of Aloe chinensis in the southwest region of China, has excellent antibiotic activity and intestine colonization ability. Here, we present the 5.8-Mb draft genome sequence of Paenibacillus sp. strain Aloe-11.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…Normally, the catalytic domains of NRPS select, activate or modify the covalently tethered reaction intermediates to control the iterative chain elongation process and product release, which occur during the ribosome-independent peptide synthesis [ 104 ]. It is important to mention that one NRPS gene cluster was discovered bearing a 30-kb DNA fragment, containing four genes ( lchAA , lchAB , lchAC , and lchAD ) involved in the biosynthesis of surface-active lipopeptides, such as lichenysin [ 105 , 106 ].…”
Section: Endophytes As Potential Producers Of Peptidesmentioning
confidence: 99%
“…Normally, the catalytic domains of NRPS select, activate or modify the covalently tethered reaction intermediates to control the iterative chain elongation process and product release, which occur during the ribosome-independent peptide synthesis [ 104 ]. It is important to mention that one NRPS gene cluster was discovered bearing a 30-kb DNA fragment, containing four genes ( lchAA , lchAB , lchAC , and lchAD ) involved in the biosynthesis of surface-active lipopeptides, such as lichenysin [ 105 , 106 ].…”
Section: Endophytes As Potential Producers Of Peptidesmentioning
confidence: 99%
“…Gut microbiota contains hundreds to thousands of bacteria obtained from a specific diet [16]. Li et al (2012) found that Paenibacillus sp. strain Aloe-11 had excellent intestine colonization ability and could significantly promote forage fiber degradation, thus producing antibiotic activity against many pathogenic bacteria and fungi [17].…”
Section: Introductionmentioning
confidence: 99%
“…Li et al (2012) found that Paenibacillus sp. strain Aloe-11 had excellent intestine colonization ability and could significantly promote forage fiber degradation, thus producing antibiotic activity against many pathogenic bacteria and fungi [17]. Likewise, Zheng et al (2020) found that a proportion of the intestinal microbes of potato tuber moth might be derived from bacterial endophytes in potatoes [18].…”
Section: Introductionmentioning
confidence: 99%